The Rise of Algerian Nationalism after the Great war - KHIREDDINE, Amel (University of El-oued, 2024)
Abstract This paper aims at underscoring that notwithstanding its detrimental worldwide repercussions, the Great War was a decisive watershed in the history of Algerian nationalism. It was the momentum that rekindled the nationalist movement in Algeria which reached its summit in the 1954 War for Liberation. The paper will shed light on the incentives that gave rise to the Algerian nationalist movement in the post First World War era as well as its leading nationalist figures. Those leaders were divided between gradualist reformers namely Young Algerians, Emir Khaled and Ferhat Abbas and those who opposed assimilationist reforms and pleaded for an independent Algeria most notably the Ulema led by Ben Badis and which stressed the Arab and Islamic roots of the country as well as Star of North Africa. The latter, under the leadership of Messali Hadj, was more radical in its nationalist claims by demanding a full liberation of the country.
Article .Ex Professo. Vol 06. N 01. Université d'El-Oued
Keywords: Keywords : First World War; Algerian Nationalism; Ferhat Abbas; Abdel Hamid Ben Badis; Messali Haj.